PENGUATAN PERAN KADER SEBAGAI AGEN PROMOTIF-PREVENTIF DALAM PENCEGAHAN KOMPLIKASI STROKE PADA LANSIA HIPERTENSI - Mira Asmirajanti; Rini Handayani; Dwi Nurmawaty; Yulhendri Yulhendri; Dessy Septianingsih; Riska Dwi Damai Yanti; Umairoh Vilfaladah; Bella Suci Cahyanti; Putri Nabila (Jurnal Abdi Insani, 2026)
Hypertension is a major risk factor for stroke among the elderly, leading to various complications and decreased quality of life. The role of community health volunteers (cadres) as promotive and preventive agents is crucial in preventing stroke complications at the community level. However, limited knowledge and practical skills among cadres remain a significant challenge. This community service activity aimed to strengthen the capacity of elderly Posbindu cadres in preventing stroke complications among hypertensive elderly through health education and hypertension exercise training. This study employed a participatory approach involving education sessions, demonstrations, and hands-on practice for 25 Posbindu cadres in Kalianyar Subdistrict, West Jakarta. Evaluation was conducted using pre-test and post-test to assess knowledge improvement, as well as observation to evaluate cadres’ skills in performing hypertension exercises. The results showed an increase in the average knowledge score from 81.36 to 90.6 after the intervention. In addition, cadres were able to perform and independently guide hypertension exercises. These findings indicate that education and practical training effectively improve both knowledge and skills of cadres. In conclusion, strengthening the role of cadres through education and hypertension exercise training is an effective strategy to enhance their capacity as promotive and preventive agents in preventing stroke complications among hypertensive elderly. This program has the potential to be replicated in other communities to support community-based health promotion.